2017
DOI: 10.1002/jbio.201700060
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin kinetics and effects on lung cancer cell lines using in vitro Raman micro‐spectroscopy: binding signatures, drug resistance and DNA repair

Abstract: Raman micro‐spectroscopy is a non‐invasive analytical tool, whose potential in cellular analysis and monitoring drug mechanisms of action has already been demonstrated, and which can potentially be used in pre‐clinical and clinical applications for the prediction of chemotherapeutic efficacy. To further investigate such potential clinical application, it is important to demonstrate its capability to differentiate drug mechanisms of action and cellular resistances. Using the example of Doxorubicin (DOX), in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 71 publications
4
46
0
Order By: Relevance
“…Farhane et al , in a comparative study between the 2 lung cancer cell lines A549 and Calu‐1 exposed to DOX at the dose corresponding to the IC 50 of each, demonstrated that, despite the fact that there is a much faster uptake of DOX and cellular saturation in Calu‐1 cells (Figures A and B), they are more resistant than A549 cells and exhibit earlier evidence of a secondary mechanism of action of DOX, by ROS production . In fact, Raman investigations show that the accumulation of DOX in the cytoplasmic area happens due to nuclear disruption, and as a consequence, the ROS production starts only after nuclear saturation, and that the 2 mechanisms of action, nucleic acid intercalation and ROS production, do not happen simultaneously.…”
Section: Raman Microspectroscopy To Distinguish Cellular Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Farhane et al , in a comparative study between the 2 lung cancer cell lines A549 and Calu‐1 exposed to DOX at the dose corresponding to the IC 50 of each, demonstrated that, despite the fact that there is a much faster uptake of DOX and cellular saturation in Calu‐1 cells (Figures A and B), they are more resistant than A549 cells and exhibit earlier evidence of a secondary mechanism of action of DOX, by ROS production . In fact, Raman investigations show that the accumulation of DOX in the cytoplasmic area happens due to nuclear disruption, and as a consequence, the ROS production starts only after nuclear saturation, and that the 2 mechanisms of action, nucleic acid intercalation and ROS production, do not happen simultaneously.…”
Section: Raman Microspectroscopy To Distinguish Cellular Resistancementioning
confidence: 99%
“…Raman spectroscopic analysis of drug-cell interactions has focused both on changes in the cellular Raman spectra upon drug application, and also during intracellular tracking of the drug and its metabolites [1,27,50,51,63].…”
Section: Raman Microspectroscopy For Chemotherapeutic Pre-clinical mentioning
confidence: 99%
“…Characterization of disease‐specific, intracellular biochemical changes becomes crucial to advance our understanding of the pathogenesis of diseases . Raman spectroscopy proved to be a valuable tool in cellular and subcellular investigations, enabling detection and localization of biochemical changes on development of pathologies, as well as investigation of various cellular events . Detection of inelastically scattered photons produces a Raman spectrum with bands corresponding to the vibrational frequencies of bonds in molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the difference in monochromatic light with vibrational modes, Raman spectroscopy can be used for qualitative and quantitative measures of the changes in biochemical composition. For example, Raman spectroscopy was used as a noninvasive method to distinguish cells at different stages in the cell cycle [90]; to identify living cells from dead cells [91][92][93][94][95]; to image cellular organelles [96]; to track drug distribution [97] and metabolism [91]; to monitor cell apoptosis [94], death, and cytotoxicity [92,95]; and to study cell responses to external stimuli [97][98][99][100][101]. However, the analysis of Raman results requires expertise in identifying the spectroscopic fingerprint of a substance.…”
Section: Raman Spectroscopy Analysismentioning
confidence: 99%